2004
DOI: 10.7326/0003-4819-140-7-200404060-00017
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Counseling Interventions in Primary Care To Reduce Risky/Harmful Alcohol Use by Adults: A Summary of the Evidence for the U.S. Preventive Services Task Force

Abstract: Behavioral counseling interventions for risky/harmful alcohol use among adult primary care patients could provide an effective component of a public health approach to reducing risky/harmful alcohol use. Future research should focus on implementation strategies to facilitate adoption of these practices into routine health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
507
2
16

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 655 publications
(531 citation statements)
references
References 77 publications
6
507
2
16
Order By: Relevance
“…23,24 Moreover, monitoring alcohol consumption of different population segments is necessary to develop effective dependence control actions and harm reduction strategies.…”
Section: Descritores: Alcoolismo Epidemiologia Fatores De Risco Famentioning
confidence: 99%
“…23,24 Moreover, monitoring alcohol consumption of different population segments is necessary to develop effective dependence control actions and harm reduction strategies.…”
Section: Descritores: Alcoolismo Epidemiologia Fatores De Risco Famentioning
confidence: 99%
“…2 Randomized controlled trials have demonstrated that brief counseling interventions in primary care settings can decrease alcohol misuse. [3][4][5][6] Alcohol screening is therefore recommended to identify patients who benefit from such interventions. 7 Although older screening questionnaires such as the CAGE were developed to identify only alcohol use disorders (definitions, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Receipt of brief intervention was defined as a Byes^response to the following question: BIn the past 12 months, has a VA doctor or other VA healthcare provider advised you about your drinking (to drink less or not to drink alcohol)?^This question has previously been used as a proxy for brief intervention because alcohol-related advice is a central component of evidencebased brief intervention. 10,37 Primary Outcomes: Patient-Reported Indicators of HighQuality Care. The following patient-reported indicators of high-quality care comprised the primary study outcomes: 1) patient report of high-quality care from their VA provider and 2) patient report of high-quality care from the VA. We assessed these outcomes using two survey questions from the CAHPS Clinician & Group Survey: BUsing any number from 0 to 10, where 0 is the worst personal doctor/nurse possible and 10 is the best personal doctor/nurse possible, what number would you use to rate your personal VA doctor/nurse?^and BUsing any number from 0 to 10, where 0 is the worst healthcare possible and 10 is the best healthcare possible, what number would you use to rate all your VA healthcare in the last 12 months?^Potential scores ranged from 0 to 10, which we dichotomized ≥ 9 according to CAHPS guidelines as indicative of high quality.…”
Section: Methodsmentioning
confidence: 99%